Situational Leadership in Islam: An Analysis of the Leadership Model of the Prophet Muhammad - Husnul Mirzal; Sri Yayu Ninglasari (Dialogia: Islamic Studies and Social Journal, 2021)
In the development of leadership studies, various leadership styles have been born. Among the various models, situational leadership is the ideal leadership style because it can adapt the leadership approach with the reality of the followers' social context and circumstances. This study examines the empirical reality practices of situational leadership in Islam by analyzing the Prophet Muhammad's leadership model. This study uses a library research method with a content analysis approach. This study's results indicate that the Prophet Muhammad used a situational leadership style in leading the ummah. This is evidenced by the Prophet's leadership characteristics between Mecca and Medina's periods, which were adapted to the social realities and conditions of his followers. The differences in leadership characteristics can be assessed through the different characteristics of the verses and hadiths used by the Prophet as a medium in leading. Besides, evidence can also be obtained through the principle of graduality in implementing Islamic teachings. The Prophet's leadership in spreading Islamic teachings is implemented gradually following the reality of the social context and the abilities of his followers.